Comparison Of Maternal And Perinatal Outcome Of Isolated Borderline Amniotic Fluid Index Versus Normal Amniotic Fluid In Low-Risk Pregnancies At Term - Kalsoom, Shabana; Majeed, Noreen Majeed; Riaz, Mamoona; Mehdi, Mehreen; Asif, Khair-un-Nisa; Mushtaq, Iram (Journal of Rawalpindi Medical College, 2023)
Objective: The objective of the study was to compare the maternal and perinatal outcomes in low-risk pregnancies having borderline Amniotic fluid index with normal amniotic fluid index at term. Methods: This prospective observational study, included 540 low-risk pregnant women admitted at POF Hospital Wah Cantt between 1st June 2020-31st Dec 2022. Group A had 180 women with borderline AFI having normal umbilical artery Doppler and group B had 360 women with normal AFI between 37-40 weeks, who fulfilled the inclusion criteria. The data regarding baseline characteristics and fetomaternal outcome was collected on an already designed proforma and analysis was done by using SPSS version 23. Results: The difference in overall cesarean section rate (p=0.071) and cesarean section for fetal distress (p=0.076) was not statistically significant between the two groups. The borderline AFI did not increase the risk of meconium-stained liquor (p=0.116), 5minute APGAR score <7 (p=0.218), admission to NICU (p=0.064) and low birth weight (mean birth weights p=0.278) compared to normal AFI. Conclusion: Borderline oligohydramnios does not increase the risk of cesarean section and cesarean section for fetal distress. There is no increase in the risk of meconium-stained liquor, 5-minute APGAR score<7, admission to NICU and low birth weight. Keywords: Amniotic fluid index, borderline oligohydramnios, cesarean section, fetal distress, meconium-stained liquor.